Relationship between school environment and job dissatisfaction among secondary school teachers in Klang, Selangor - Subramaniam, Sivagamy; Abdul Kadir, Suhaida (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Job Dissatisfaction is defined as an unpleasant feeling of an employee towards their work. This study was conducted to examine the relationship between the school environment and job dissatisfaction among secondary school teachers in Klang, Selangor. The study was conducted in four secondary schools in Klang, Selangor. In this study, quantitative method has been used where questionnaire was used in this study to obtain data from the respondents. School Environment was measured using the modified School-Level Environment Questionnaire (SLEQ) (Rentoul and Fraser.1983), where else questionnaire for Job Dissatisfaction was adopted from Hagedoorn.et.al. (1999). Total 181 questionnaires were collected and analyzed for the findings. The analysis showed the overall mean for job dissatisfaction is low (M=2.31, SD=.37), while the mean for school environment is at moderate level (M=3.08, SD=.38). Pearson correlation analysis found there is moderate negative relationship between School Environment and Job Dissatisfaction (r = -.640, p<.01). These findings shows that future studies should focus on the reasons teachers are dissatisfied with school environment and ways to overcome it.